Current Perspective on the Role of the Thrombin Receptor in Cerebral Vasospasm After Subarachnoid Hemorrhage - Katsuya Hirano; Mayumi Hirano (Elsevier, 2010)
Cerebral vasospasm is a persistent arterial narrowing typically observed during the 3 - 14 days after subarachnoid hemorrhage (SAH). Vasospasm is frequently associated with ischemic neurological deficits or even death, resulting in a poor prognosis for patients with SAH. However, the mechanism underlying cerebral vasospasm remains elusive, and no effective therapeutic strategies have been established. A large amount of thrombin is produced during SAH. Recent investigations have uncovered a key role of the thrombin receptor in the pathogenesis of cerebral vasospasm. Thrombin has little contractile effect in the normal cerebral artery, but it induces an enhanced and prolonged contraction after SAH, owing to the up-regulation of thrombin receptor PAR1 (proteinase-activated receptor 1) and the impairment of receptor desensitization in arterial smooth muscle. Thrombin-mediated activation of PAR1 is an irreversible process, as it is initiated by the proteolytic removal of the N-terminal region. Since the mechanism of receptor desensitization is impaired after SAH, the thrombin-induced contraction irreversibly persists even after terminating thrombin stimulation. Intrathecal administration of a PAR1 antagonist prevents the PAR1 up-regulation and the increased reactivity to thrombin. PAR1 is suggested to play a key role in cerebral vasospasm and may be useful as a therapeutic target for prevention and treatment of cerebral vasospasm. Keywords:: desensitization, proteinase-activated receptor, up-regulation, subarachnoid hemorrhage, vasoconstriction